Development of gamification as addiction education and examining its effects on students’ motivation and enjoyment (Bangladesh Journal of Medical Science, 2023)
Introduction Addiction is a “social disease” which has physical and mental effects. Having adequate knowledge and information about addiction is the best way to prevent it in the community. The current study aims to focus on developing gamification as addiction education and examining its effects on students’ motivation and enjoyment.Methods: This is guise experiment for gamification development and assess educational intervention. Educational and technical standards have been considered for the development of gamification. In technical standards, it is congruent with the app-making technology based on dynamism, mechanisms and dynamic gamification. This game is available on www.addiplay.ir website through Microsoft Aps net core technology. Educational intervention implied on two groups of medical students and Public Health students and learning indicators assessed through intervention.Results; The findings of this study on two groups of students showed that, the game can influence on students’ enjoyment and consent. In addition, the game had a high average in increasing learners’ ability and students satisfaction. One of the limitations of gamification has been its dependence on each learner’s ability.Conclusion: The results showed that new teaching and learning methods such as gamification in addiction lessons in a mixed and complimentary way can fulfill the educational goals instead of written handbooks or traditional classes and makes learning possible in a motivated and entertaining environment.Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 564-572